HUKUM PEMIMPIN IDEAL DALAM PERSPEKTIF HADIS - Samud Samud (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
Times developmentÂ will have a tremendous influence on the condition of the country and society, as in the near future the election of leaders will soon begin at both central and regional level leaders. It turns out that the election of leaders now seems to be an extraordinary gambling event because each political party appoints one of its cadres to become the number one person in our country. The ideal leader in the advice of Islam should be able to be included in the meaning of helper, because the leader is in charge of protecting the people he leads and trying to help and save them when difficulties and disasters strike, because the leader is responsible for everything that happens and happens in his area and about the people they lead. A leader is chosen to lead his group members to realize common goals.